Measurement of the Attractiveness of Public Open Spaces to Visitors at Lifestyle Centers - Afliyah Harni Nasution (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to measure the attractiveness of public open spaces to visitors in Lifestyle Centers using a modified Urban Mobility Index (I-MUS). The background of this research is based on the importance of mobility in the tourism sector, where transportation mobility plays a role in facilitating tourist access to various destinations. The research method uses a quantitative approach by adapting the I-MUS framework consisting of 6 domains, 16 sub-domains, and 46 variables. Data was collected through a closed questionnaire method involving experts from the Ministry of Transportation, local governments, and academics. The results of the analysis using the Content Validity Index (CVI) showed that of the initial 32 variables, 6 variables were declared invalid. The final results show that the attractiveness of public open spaces in the Lifestyle Center is influenced by 26 main variables divided into 5 domains. This research makes a significant contribution to the development of tourism in Indonesia by providing measurement tools that can be used to monitor and improve tourism mobility in various destinations.